Appearance of renal hemorrhage in adult mice after inoculation of patient-derived hantavirus. Issue 1 (December 2017) - Shimizu, Kenta; Koma, Takaaki; Yoshimatsu, Kumiko; Tsuda, Yoshimi; Isegawa, Yuji; Arikawa, Jiro
Abstract Background Hemorrhagic fever with renal syndrome (HFRS) caused by hantavirus infection is characterized by fever, renal dysfunction and hemorrhage. An animal model mimicking symptoms of HFRS remains to be established. In this study, we evaluated the pathogenicity of an HFRS patient-derived Hantaan virus (HTNV) in adult mice. Methods Five clones of HTNV strain KHF 83-61 BL (KHFV) that was derived from blood of an HFRS patient were obtained by plaque cloning. The pathogenicity of the virus clones was evaluated by using 6-week-old female BALB/c mice. Sequence analysis of the viral genome was performed by conventional methods. Results All of the mice intravenously inoculated with KHFV clone (cl)-1, -2, -3 and -5 showed signs of disease such as transient body weight loss, ruffled fur, reduced activity and remarkably prominent hemorrhage in the renal medulla at 6 to 9 days post-inoculation (dpi) and then recovered. In contrast, mice intravenously inoculated with KHFV cl-4 did not show any signs of disease. We selected KHFV cl-5 and cl-4 as representative of high-pathogenic and low-pathogenic clones, respectively. Quantities of viral RNA in kidneys of KHFV cl-5-infected mice were larger than those in KHFV cl-4-infected mice at any time point examined (3, 6, 9 and 12 dpi). The quantities of viral RNA of KHFV cl-5 and cl-4 peaked at 3 dpi, which was before the onset of disease. Sequence analysis revealed that the amino acid at position 417 in the glycoprotein Gn was the sole difference in viral proteins between KHFV cl-5 and cl-4. The result suggests that amino acid at position 417 in Gn is related to the difference in pathogenicity between KHFV cl-5 and cl-4. When the inoculum of KHFV cl-5 was pretreated with a neutralizing antibody against HTNV strain 76-118, which belongs to the same serotype as KHFV clones, mice did not show any signs of disease, confirming that the disease was caused by KHFV infection. Conclusion We found that an HFRS patient-derived HTNV caused renal hemorrhage in adult mice. We anticipate that this infection model will be a valuable tool for understanding the pathogenesis of HFRS.